2022
DOI: 10.9734/jammr/2022/v34i731331
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Admission into the Department of Paediatric Bingham University Teaching Hospital (BHUTH) Jos

Abstract: Introduction: The Coronavirus disease 2019 (COVID 19) pandemic has a significant impact on global health systems, not only in terms of the number of people infected with the disease, but also in terms of patients with other diseases. The COVID-19 pandemic, as well as the measures taken to combat it, such as complete lockdown, has a significant impact on health seeking behaviour and the health care-delivery system. Studies have shown that while COVID-19 confirmed cases have gradually increased, visits to hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The COVID 19 pandemic had a significant impact on the health sector. 6,9,21 Our study revealed a general decrease in the number of children presenting to the hospital during the pandemic with various illnesses (like malaria, diarrhoeal diseases and other respiratory tract infections among others) including pneumonia. This finding is at par with that of various studies carried out in other parts of the world like Japan, Italy, France and the United States of America.…”
Section: Discussionmentioning
confidence: 74%
“…The COVID 19 pandemic had a significant impact on the health sector. 6,9,21 Our study revealed a general decrease in the number of children presenting to the hospital during the pandemic with various illnesses (like malaria, diarrhoeal diseases and other respiratory tract infections among others) including pneumonia. This finding is at par with that of various studies carried out in other parts of the world like Japan, Italy, France and the United States of America.…”
Section: Discussionmentioning
confidence: 74%